Amplitude modulation of oscillatory activity in the subthalamic nucleus during movement. - Androulidakis, A; Brücke, C; Kempf, F; Kupsch, A; Aziz, T; Ashkan, K; Kühn, A; Brown, P (2008)
Depth recordings in patients with Parkinson's disease (PD) have demonstrated exaggerated local field potential (LFP) activity at frequencies between 10 and 30 Hz in the subthalamic nucleus (STN). This activity is modulated prior to single phasic movements, possibly as part of the feedforward organization of incipient voluntary movement, and after single phasic movements, as a consequence of afferent feedback processes. Here we test the hypothesis that this activity is also modulated during repetitive movements, reflecting a role in ongoing performance. Accordingly, we recorded LFP activity from the contralateral STN of seven patients with PD withdrawn from anti-parkinsonian medication while they performed repetitive index finger to thumb taps. Cross-correlograms of LFP activity at different frequencies in the 10-30 Hz band with finger position showed that LFP activity was modulated in amplitude by finger tapping. The modulation was higher at the beginning of each recording when tapping performance was better, and diminished as tapping became more bradykinetic over time. The best modulations were seen over those frequencies that were maximal in the power spectrum of the corresponding LFP, and for a given side were most marked at the contact pair that exhibited the highest power at these frequencies. In conclusion, subthalamic activity in the 10-30-Hz band is amplitude modulated during movement. This process fails as bradykinesia increases.